REFORM OF JAPAN'S NTP AND ITS TECHNICAL PERSPECTIVES: The 79th Annual Meeting Special Lecture - MORI, Toru (Kekkaku(Tuberculosis), 2004)
The 1951 Tuberculosis Control Law of Japan is now faced with tremendous changes that have occurred during the last 50 years in tuberculosis epidemiology and in the environment in tuberculosis control implementation. The law is also challenged with the shift of the paradigm for the National Tuberculosis (TB) Programme. In order to respond properly to these changes, the Tuberculosis Panel of the Health Science Council of the Ministry of Health, Labor and Welfare submitted its report for the amendment of the law in March 2002. Based on this report, a new Tuberculosis Control Law was passed in Parliament last June, and related decrees of the Cabinet and the Ministry are now being revised in preparation for it's enactment in April 2005. In this special lecture, the main points and framework of the revisions were discussed with the perspective of the development of new technical innovations relevant to each area of the revised TB control legislation. 1. Case detection. There will be a shift from the current “indiscriminate” screening scheme to a selective one regarding periodic mass health examination. Only subjects aged 65 or older will be eligible for the screening, supplemented with selected occupational groups who are considered to be at a higher risk of TB, or may be a danger to others if they develop TB, such as health-care providers and school teachers. In addition, local autonomies are responsible for offering screening to the socio-economic high-risk populations, such as homeless people, slum residents, day laborers, and/or workers in small businesses. This means that the efforts of the autonomies are critical for the new system to be effective. The extraordinary examination will be limited to only the patient's contacts, and will be mandatory for those contacts so they cannot refuse to be examined by the Health Center. The public services used in the contact investigations will be greatly facilitated by such new technologies as DNA fingerprinting of TB bacilli and a new diagnostic of TB infection using wholeblood interferon-gamma determination (QuantiFERON). The quality of clinical diagnosis and monitoring of treatment should also be improved by introducing an external quality assurance system of commercial laboratory services. 2. Chemoprophylaxis. Although not explicitly defined in the new legislation, the expansion and improvement of chemoprophylaxis to cover anyone with any risk of clinical development of TB would have a tremendous effect in Japan, especially since 90% of patients who developed TB were infected tens of years ago. These technical innovations in diagnosis of TB infection will be very helpful. Development of new drug regimens for the preventive treatment is also badly needed.